Preparation and evaluation of molecularly imprinted polymer liquid chromatography column for the separation of ephedrine enantiomers - Krishnamoorthy balamurugan (Arabian Journal of Chemistry, 2016)
In this study molecular imprinting technology was employed to prepare a specific affinity sorbent for the resolution of Ephedrine, a chiral drug. The molecularly imprinted polymer (MIP) was prepared by non-covalent molecular imprinting with either (+) or (-)-Ephedrine ((R∗,S∗)-2-(methylamino)-1-phenylpropan-1-ol) as the template. Methacrylic acid and ethylene glycol di-methacrylate were copolymerized in the presence of the template molecule. The bulk polymerization was carried out in chloroform with 2,2′-azobisisobutyronitrile as the initiator, at 5°C and under UV radiation. The resulting MIP was ground into powders, which were slurry packed into analytical columns. After removal of template molecules, the MIP-packed columns were found to be effective for the resolution of (±)-Ephedrine racemates. The separation factor for the enantiomers ranged between 1.3 and 2.1 when the column was packed with MIP prepared with (+)-Ephedrine as the template. A separation factor ranging from 1.3 to 2.6 could be achieved from the column packed with MIP, prepared with (-)-Ephedrine as the template. Although the separation factor was higher with that previously obtained from reversed-phase column chromatography following derivatization with a chiral agent, elution peaks were broader due to the heterogeneity of binding sites on the MIP particles and the possible non-specific interaction.